1998
DOI: 10.1017/s0007485300026031
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variability within and between English populations of the damson–hop aphid,Phorodon humuli(Hemiptera: Aphididae), with special reference to esterases associated with insecticide resistance

Abstract: The damson-hop aphid, Phorodon humuli (Schrank), is a serious pest of hops in England. It is holocyclic (with obligatory sexual phase) and host alternating. From suction trap data, P. humuli aerial densities are known to be greatest in the main hop growing regions of Herefordshire and Kent (mid-west and south-east England, respectively), some 260 km apart. The aphid is now resistant to several insecticides. This is in part conferred by elevated carboxylesterase activity, ranging from low in susceptible to high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 39 publications
1
17
0
Order By: Relevance
“…The existence of host-mediated genetic differentiation is relevant for the analysis of the ecological causes that promote differentiation (Nason et al, 2002). The genetic structure of aphid species is maintained by selection adjusting populations to the local environmental conditions (Tomiuk and Wö hrmann, 1984;EggersSchumacher and Sander, 1988;Tomiuk et al, 1991), by reduced gene flow (Loxdale and Brookes, 1990;Loxdale et al, 1998;Johnson et al, 2002;Massonnet et al, 2002), itself a function of species-specific flight behaviour dependent on their tendency and their ability to fly (see Loxdale et al, 1993, for a review), and by genetic drift (De Barro et al, 1995a). Perhaps, as in the case of the aphid Methopolophium dirhodum, differentiation between hosts in the localities of Mitzitón and Balú n could be better explained if founder effects or genetic drift have occurred (see De Barro et al, 1995a).…”
Section: Discussionmentioning
confidence: 99%
“…The existence of host-mediated genetic differentiation is relevant for the analysis of the ecological causes that promote differentiation (Nason et al, 2002). The genetic structure of aphid species is maintained by selection adjusting populations to the local environmental conditions (Tomiuk and Wö hrmann, 1984;EggersSchumacher and Sander, 1988;Tomiuk et al, 1991), by reduced gene flow (Loxdale and Brookes, 1990;Loxdale et al, 1998;Johnson et al, 2002;Massonnet et al, 2002), itself a function of species-specific flight behaviour dependent on their tendency and their ability to fly (see Loxdale et al, 1993, for a review), and by genetic drift (De Barro et al, 1995a). Perhaps, as in the case of the aphid Methopolophium dirhodum, differentiation between hosts in the localities of Mitzitón and Balú n could be better explained if founder effects or genetic drift have occurred (see De Barro et al, 1995a).…”
Section: Discussionmentioning
confidence: 99%
“…The smallest mean catches occurred in the Porma river. This may be because the intensity of hop cultivation in that area is lower than in the other areas; even though, according to Loxdale et al (1998) and Taylor et al (1979), P. humuli migrants can disperse over great distances. in the more intensive hop producing areas, Moericke traps captured more specimens of P. humuli than the suction trap (Table 1).…”
Section: Resultsmentioning
confidence: 94%
“…It has been shown that the esterase variation corresponds with resistance to organophosphorus insecticides in certain aphid species as mentioned above. The effort to control the aphids led to increased insecticide usage and, consequently, higher esterase variants had been selected Loxdale et al, 1998;Guillemaud et al, 2003). In England, the progressive decline in levels of esterase resistance in M. persicae collected between 1996 and 2000 was most probably driven by fitness costs coupled with generally reduced insecticide selection pressure from 1997 onwards (Foster et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…As the circumstances change, the esterase composition of the aphid drastically changes with them on a short timescale (Foster et al, , 2002Shigehara and Takada, 2003). The other interpretation is that such differences resulted from a founder effect (Fuentes-Contreras et al, 2004) or restriction of gene flow (Loxdale et al, 1998). The low migratory ability of A. solani would contribute to build-up of peculiar esterase compositions due to differentiating forces other than selection.…”
Section: Discussionmentioning
confidence: 99%